Simple algorithm for semi-active seismic response control of cable-stayed bridges. - Iemura, Hirokazu (Earthquake engineering & structural dynamics.)
The linear quadratic regulator (LQR) control algorithm is at the heart of many modern control design methods. There have been numerous publications dealing with LQR control and earthquake engineering. However, very few papers discuss the hysteretic loops produced by the LQR control force, although in the earthquake engineering field, hysteretic loops have been the key part of seismic designs. This paper shows the importance of investigating the hysteretic loops produced by the LQR control force, although in the earthquake engineering field, hysteretic loops have been the key part of seismic designs. This paper shows the importance of investigating the hysteretic loops produced by the LQR control force, although in the earthquake engineering field, hysteretic loops have been the key part of seismic designs. This paper shows the importance of investigating the hysteretic loops produced by the LQR control force for seismic response, and proposes a method to reproduce the hysteretic loops with a much simpler algorithm. The investigation was carried out on a cable-stayed bridge model controlled either by the LQR algorithm, viscous damper, or the proposed method. The results show that the proposed method is capable of reducing seismic response better than the viscous damper case and is similar to the LQR case. The practical applicability of the proposed method is also investigated by using a variable orifice oil damper as the controlling device. The proposed method needs only displacement response at the device location, and therefore fewer sensors are needed than for the LQR algorithm.